Marketing Strategy (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
A marketing strategy is an overview of how a business or organization will articulate its value proposition to its customers. Generally, a marketing strategy outlines business goals, target market, buyer personas, competitors, and value for customers.